Duplication and nonregistration of COVID‐19 systematic reviews: Bibliometric review. Issue 3 (21st April 2022) - Helliwell, Jack A.; Thompson, Joe; Smart, Neil; Jayne, David G.; Chapman, Stephen J.
Abstract: Objectives: This study examines the conduct of systematic reviews during the early stages of the COVID‐19 pandemic, including compliance to protocol registration and duplication of reviews on similar topics. The methodological and reporting quality were also explored. Methods: A cross‐sectional, bibliometric study was undertaken of all systematic review manuscripts on a COVID‐19 intervention published between January 1st and June 30th, 2020. Protocol registration on a publicly accessible database was recorded. Duplication was determined by systematically recording the number of reviews published on each topic of analysis. Methodological quality and reporting quality were assessed using the AMSTAR‐2 and PRISMA 2009 instruments, respectively. Results: Thirty‐one eligible systematic reviews were identified during the inclusion period. The protocol of only four (12.9%) studies was registered on a publicly accessible database. Duplication was frequent, with 15 (48.4%) of the 31 included studies focusing on either hydroxychloroquine (and/or chloroquine) or corticosteroids. Only one study (3.2%) was of "high" methodological quality, four (12.9%) were "low" quality, and the remainder ( n  = 26, 83.9%) were of "critically low" quality. The median completeness of reporting was 20 out of 27 items (74.1%) with a range of 5–26 (interquartile range: 14–23). Conclusion: Systematic reviews during the early stages of the COVID‐19 pandemic were uncommonly registered, frequently duplicated, and mostly of low methodological quality. In contrast, the reporting quality of manuscripts was generally good but varied substantially across published reports. There is a need for heightened stewardship of systematic review research, particularly during times of medical crisis where the generation of primary evidence may be rapid and unstable.